Cidades inflamáveis: procedimento operacional para comunicação de incêndios urbanos no centro histórico de Diamantina - Minas Gerais - Helena Rosmaninho Alves Moreira Gonçalves (2022)
This research aims to discuss the creation of an operational procedure for the communication of urban fires in historic cities, based on Diamantina – Minas Gerais. Integrating the Culture and Tourism Department (SECTUR), as an agent of the Civil Defense System, being responsible for the communication of disasters within the historic center, protecting people and goods. The proposed methodology creates the organization of the communication strategy, suggesting the creation of a mobile application, capable of identifying the exact location of the adverse event, presenting an escape route, support points and in case of imminent danger, call the competent authorities. The use of applications as a means of managing time and space has been part of everyday life today. Disaster management can and should accompany the use of these technologies insofar as it visually presents the risks and safety measures to be taken, promotes the well-being of populations, mitigates the state of vulnerability, managing risk and disasters. The objective of this thesis is to create an operational procedure for disaster communication capable of mitigating the damage caused by the intervention, ensuring through effective communication the physical integrity of the property and the protection of human life, following a Disaster Risk Management methodology based on the Sendai landmark.